PRINSIP KOMUNIKASI ISLAM TENTANG DIALOG (Kajian Kepustakaan terhadap Komunikasi Interpribadi) - Rosniar Rosniar (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
Abstract Dialogue does not always aim to resolve disputes, but rather aims to develop a shared understanding of a complex topic. Dialogue is a form of structured interpersonal communication, relying on full attention, involving all parties to argue and listen actively. Dialogue is different from debate because debate always offers two points of view with the aim of proving the validity or truth of one perspective against another. Therefore, dialogue does not only involve the mind but also the heart because in interactions it has ethical standards in communication and its relationship with the Islamic communication strategy that commands Allah Subehanahu Wata'ala in the Koran. To obtain representative data, a library research approach is used by searching, collecting, reading, and analyzing books, literature, and documents that are relevant to this research problem. The data collected is then analyzed using a scientific approach to Islamic Communication, so that a result is found that reveals that dialogue should be carried out by allowing people to understand the perspectives of others without ignoring a different perspective of oneself. In the form of interpersonal relationships that are bound by topics or themes that can be explored together by thinking objectively based on the principles of Islamic communication, namely qaulan sadidan (true, not lying); qaulan baligha (straightforward, effective); qaulan ma’rufa (kind and polite words); qaulan karima (respect, respect); Qaulan Layina (Gentle); And Qaulan Maysura (Easy to Understand). Keywords: Principles, Islamic Communication, Dialogue, Interpersonal Communication.